PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA INNOVA PADA PT. AGUNG TOYOTA (AUTOMALL) SM. AMIN PEKANBARU - Angga Aditia; Eka Komalasari (VALUTA, 2021)
This research was aimed to find out and analyze the influence of product quality toward the purchase decision of Toyota Innova cars at PT. Agung Toyota (Automall) SM. Amin Pekanbaru. The sample in this research is Toyota innova cars buyer of 58 consumers at PT. Agung Toyota SM. Amin. The sampling tecnhnique taken was through Porposive sampling is a sampling tecnhnique with certain considerations. The type of research used was descriptive research with simple linear regression. Method data analysis used to calculate is using validity test, reliability test, normality test, hypothesis test and t- test. Based on the analysis and simple linear regression that product quality variables have a positive influence on purchasing decision.